Spectrally selective emitters based on 3D Mo nanopillars for thermophotovoltaic energy harvesting. (November 2021) - Chirumamilla, Anisha; Yang, Yuanqing; Salazar, Maria H.; Ding, Fei; Wang, Deyong; Kristensen, Peter Kjær; Fojan, Peter; Bozhevolnyi, Sergey I.; Sutherland, Duncan S.; Pedersen, Kjeld; Chirumamilla, Manohar
Abstract: High-temperature stable emitters with spectral selective functionality are an absolute condition for efficient conversion of thermal radiation into electricity using thermophotovoltaic (TPV) systems. Usually, spectral selective emitters are made up of multilayered materials or geometrical structures resulting from complex fabrication processes. Here, we report a spectrally selective emitter based on a single metal layer coating of molybdenum (Mo) over a 3D dielectric pillar geometry. 3D Mo nanopillars are fabricated using large-area and cost-effective hole-mask colloidal lithography. These nanostructures show an absorptivity/emissivity of 95% below the cut-off wavelength of an InGaAsSb PV cell at 2.25 μm, and a sharp decline in absorptivity/emissivity in the near-infrared regions, approaching a low emissivity of 10%. The 3D Mo nanopillars show outstanding thermal/structural stability up to 1473 K for 24 h duration under Ar atmosphere and polarization and angle invariance up to 60° incidence angles. With a low-cost and scalable fabrication method, 3D Mo nanostructures provide tremendous opportunities in TPV and high temperature photonic/plasmonic applications. Graphical abstract: Image 1 Highlights: 3D Mo nanopillars exhibit unprecedented thermal stability at high temperatures, up to 1473 K. Spectrally selective emitters based on 3D Mo nanopillars are demonstrated for thermophotovoltaic energy harvesting. 3D Mo nanopillars are fabricated using large-area and low-cost fabrication method, hole-mask colloidal lithography.